Life in ponds and streams - Amos, William Hopkins ([Washington, D.C.] : National Geographic Society, 1981)
An introduction to the animals that live in ponds and streams, including beavers, frogs, ducks, crayfish, trout, and insects.
Keywords: Pond ecology; Stream ecology; Pond animals; Stream animals